PKM IMPLEMENTATION OF DISCUSSION AND PRESENTATION METHODS IN AN EFFORT TO INCREASE ACTIVE STUDENT PARTICIPATION ENGLISH COMPREHENSION OF GRADE 2 STUDENTS AT THAMPSTAMP WITTAYA SCHOOL - Domusor, Ahmad; Amroellah, Afif; Yuliana, Winditya; Puspitaningtyas, Amalia Risqi; Setiawan, Gustilas Ade; Zahra, Zahra (INTEGRITAS : Jurnal Pengabdian, 2025)
Community Service Program (KKN) is one of the media to hone student competence in practicing knowledge and applying the results of research that they have learned during semesters 1 to 6 at the university. Community service activities are a form of community service activities carried out by students so that they have direct experience in the community in applying the knowledge they have gained during lectures. The International KKN program is a description of the implementation of educational, research, community service activities carried out by universities abroad with the aim of increasing student outbound mobility. The low knowledge of English in the community is of course the biggest obstacle in improving the quality of foreign tourist hospitality. In this case, of course, educational programs are needed to improve the understanding of English in the community, especially students who will become the nation's successors who are still quite low in English through the implementation of discussion and presentation methods so that active student participation occurs. With this obstacle, the International Community Service Program feels responsible for providing English language improvement in order to increase the use and understanding of English at the school level. In this case, we conducted a service program of teaching and learning activities in class 2-2 of Thampstamp Wittaya School Junior High School with the aim that these students can understand the use and language of English in everyday life and be able to continue the development of the country.